Shapira’s Deuteronomy, Its Decalogue, and Dead Sea Scrolls Authentic and Forged - Klawans, Jonathan (Dead Sea discoveries, 2022)
This essay engages Idan Dershowitz’s recent attempt to rehabilitate the Deuteronomy fragments Moses Wilhelm Shapira offered for sale in 1883. After summarizing the contents of Dershowitz’s volume, this paper evaluates Shapira’s fragments in relation to the Dead Sea Scrolls, the Moabitica and other forgeries connected to Shapira. It considers the implications of Shapira’s transcription of the text, which Dershowitz uses to demonstrate Shapira’s innocence. To counter Dershowitz’s hypothesis regarding the “proto-biblical” origin of the fragments, it is proposed that the composition is better understood as a post-biblical pastiche. Dershowitz has endeavored to sever the text from the possibilities allowed by 19th century European scholarship; the present article contextualizes the find within the religious world of 19th century Jerusalem. While the allure of significance can encourage scholars to overcome doubts and accept the authenticity of suspicious objects, Shapira’s fragments remain very dubious indeed.